2012
DOI: 10.1007/s00381-012-1690-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of vincristine administered via convection-enhanced delivery in a rodent brainstem tumor model documented by bioluminescence imaging

Abstract: VCR administered by CED was effective in reducing tumors and prolonging survival time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…[10][11][12] CED can bypass the BBB to deliver therapeutic agents to the brain tumors; reduce systemic drug levels to minimize side effects; and provide prolonged elevation of intracerebral chemotherapeutic agents relative to systemic administration. 13,14 Our laboratory 15,16 and others [17][18][19][20][21] have confirmed that CED is an effective delivery method for brain tumor treatment. However, even with this delivery method, sustained localized distribution and prolonged retention after drug delivery remain major challenges.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…[10][11][12] CED can bypass the BBB to deliver therapeutic agents to the brain tumors; reduce systemic drug levels to minimize side effects; and provide prolonged elevation of intracerebral chemotherapeutic agents relative to systemic administration. 13,14 Our laboratory 15,16 and others [17][18][19][20][21] have confirmed that CED is an effective delivery method for brain tumor treatment. However, even with this delivery method, sustained localized distribution and prolonged retention after drug delivery remain major challenges.…”
Section: Introductionsupporting
confidence: 54%
“…Our previous study, 15,16 as well as work from other labs [38][39][40] had shown that bioluminescence is an ideal method for monitoring in vivo brain tumor therapeutic efficacy. In vitro results from this study showed a correlation between BLI and number of injected cells (Supplementary Figure 4).…”
Section: Therapeutic Potential Of Nd-dox In Brain Tumorsmentioning
confidence: 98%
“…Several groups have previously described the use of MRI-derived measures of tumor volume in the C6 model ( 32 ), and BLI has been used in some C6 tumors ( 33 , 34 ). Our study describes the first combined use of mpMRI and BLI to quantitatively characterize orthotopic C6 tumor growth in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Dr. Guifa Xi, who succeeded this research project in my lab, treated them with vincristine, and the results of efficacy and toxicity were published in 2011 [57]. For that study, first, vincristine toxicities after direct injection to the brain stem in a rat were tested to optimize the dosage [58]. Subsequently, rat brain stem glioblastoma was treated with vincristine administered through convection enhanced interstitial injection comparing with control, intravenous, and intraperitoneal injections.…”
Section: Brainstem Tumorsmentioning
confidence: 99%